A mechanistic investigation of the coral Mn/Ca-based trade-wind proxy at Kiritimati. (1st July 2022) - Chapman, Alice U.; Thompson, Diane M.; Hlohowskyj, Stephan R.; Carilli, Jessica E.; Gordon, Gwyneth; Goepfert, Tyler J.; Sayani, Hussein R.; Marchitto, Thomas M.; Cobb, Kim M.
Abstract: Tropical Pacific trade-wind behavior is linked to the El Niño-Southern Oscillation and Pacific Decadal Variability, which modulate the rate of climate change. Despite their importance, high-resolution trade-wind observations span only the past 30–40 years and are too sparse to assess decadal wind variability and long-term trends. Previous work demonstrated that reef-building corals growing at the tropical Pacific island of Tarawa (2°N, 165°E) exhibit spikes in the manganese-to-calcium ratio (Mn/Ca) of their skeleton in response to a reversal of trade winds (i.e., westerly winds). Records of Mn/Ca from long-lived corals therefore hold great promise as indicators of past trade-wind variability. However, at other nearby islands with west-facing lagoons, there is a lag between westerly winds and coral Mn/Ca spikes and a significant difference in the magnitude of spikes between corals. To address uncertainties in how winds are recorded by coral Mn/Ca, we assess the reservoirs of Mn in the sediment, sediment pore spaces (porewater), and water column of Kiritimati's lagoon and inland lakes (1.9°N, 157.5°W). We find that insoluble dustborne Mn, once buried in lagoon sediments, becomes reduced and more soluble, leading to its accumulation in the sediment porewater. This Mn reservoir is then released into the water column when strong westerly wind events cause sufficient water-column mixing to reach lagoonal sediments. While this mechanism is consistent with what was previously proposed at Tarawa, the concentration of dissolved porewater Mn at Tarawa is nearly 20 times greater than at Kiritimati. We attribute this difference to the water depth of the sediment core from which porewater was sampled and the time elapsed between the most recent westerly wind event and core sampling, which both influence the "recharge time" of the porewater Mn reservoir. As such, lagoon bathymetry and morphology modulate lagoon water and sediment porewater Mn concentrations, which impact how westerly winds imprint their signal onto coral Mn/Ca. Armed with an improved understanding of the mechanism behind this coral Mn/Ca-trade wind relationship, we can better assess the reliability of this coral proxy through space and time and identify optimal sites for Mn/Ca-based wind reconstructions, paving the way for critical new insights into the role of winds in future climate change.